Efektifitas Penyuluhan Kesehatan terhadap Peningkatan Sikap dan Motivasi dalam Pencegahan Anemia Defisiensi Zat Besi pada Ibu Hamil - Darmawati Darmawati; Elly Wardani; Cut Husna; Nia Saumiana (Faletehan Health Journal, 2020)
Iron deficiency anemia is the common type of anemia which is about 75% of all types of anemia and it is known as the death cause of maternal including postpartum hemorrhage, eclampsia, infectious diseases, and placenta previa. Attitude and motivation of the mother are needed to prevent iron deficiency anemia from causing this condition. One of the efforts that could be done is through health counseling. This research aimed to understand the effectiveness of health counseling toward attitude and motivation in preventing iron deficiency anemia among pregnant women. The research was an experimental study with one group pre-test post-test design. Sample collection technique implemented was quota sampling with 50 respondents. Data collection was carried out using questionnaires attitude and motivation that had been analyzed by using Wilcoxon sign test. The result showed that health counseling was effective in increasing respondent's attitude (p-value was 0.000) and motivation (p-value was 0,000), with the difference in the mean value of pre-test and post-test were 4.46 and 1.86 respectively. It is expected for health workers to improve counseling programs about iron deficiency anemia, so that pregnant women have a positive attitude and high motivation to prevent iron deficiency anemia.